2010
DOI: 10.1002/ijc.25107
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of gap junction connexin46 protein to protect breast tumors from hypoxia

Abstract: Connexin proteins are the principle structural components of the gap junctions. Colocalization and tissue-specific expression of diverse connexin molecules are reported to occur in a variety of organs. Impairment of gap junctional intercellular communication, caused by mutations, gain of function, or loss of function of connexins, is involved in a number of diseases including the development of cancer. Here we show that human breast cancer cells, MCF-7, and breast tumor tissues express a novel gap junction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 41 publications
3
55
0
Order By: Relevance
“…Cx43 has anti-tumor properties, and expression of Cx43 can be down-regulated in tumors (22)(23)(24)(25). Moreover, in previous studies, we have shown that Cx46 is up-regulated in breast tumor samples, MCF-7 xenografts, and Y79 retinoblastoma xenografts and acts as an oncogene to favor early tumor growth (24,25).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Cx43 has anti-tumor properties, and expression of Cx43 can be down-regulated in tumors (22)(23)(24)(25). Moreover, in previous studies, we have shown that Cx46 is up-regulated in breast tumor samples, MCF-7 xenografts, and Y79 retinoblastoma xenografts and acts as an oncogene to favor early tumor growth (24,25).…”
Section: Discussionmentioning
confidence: 78%
“…Immortalized HLECs and rabbit lens epithelial NN1003A cells (NN) were cultured as described previously (24). Briefly, cells were cultured in low glucose DMEM (Invitrogen) supplemented with 10% premium fetal bovine serum (Atlanta Biologicals, Atlanta, GA) to at least 70% confluence prior to use for experimentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cx46 has gained considerable attention lately as a potential target for cancer treatment (20,21) because it has been suggested that Cx46 helps cancer cells survive in hypoxic conditions (20). Because of its potential role of Cx46 in cancer biology and its sensitivity to gaseous transmitters such as NO (15), we decided to evaluate the possibility that Cx46 HCs are affected by HO-1 effectors (CO or guanylyl cyclase signaling pathways).…”
mentioning
confidence: 99%
“…Today, connexin proteins are, however, beyond gap junction (Goodenough & Paul, 2003)! A great variety of structures, functions, and behaviours of connexin proteins are known, i.e., hemichannel (Jiang & Gu, 2005), mitochondrial connexin (Boengler et al, 2005), oncogenic connexin (Banerjee et al, 2010;Boengler et al, 2005;Ito et al, 2000), cytoplasmic connexin , fragmented connexin, and then, gap junction. Therefore, the functions of connexin proteins in cancers are not always suppressive to either cell proliferation or tumour progression (Naus & Laird, 2010).…”
Section: Conclusive Remarksmentioning
confidence: 99%